Control Strategies for Power Quality in Rural Microgrids (2017)
In this paper we review about some control techniques used in electrical microgrids, with a special emphasis on those used for the operation in island mode, which is an expected feature in rural microgrids. On the other hand, the dispatch management is presented as a control strategy that impacts the energy quality of the microgrid associated with the concept of Hosting Capacity, which, in this specific case, it refers to the restrictions the system may have about chargeability given the generation. Finally, it is important to mention that this work was developed in the framework of the project: “Incremento en las estrategias sustentables en el uso del recurso de energía eléctrica para la población vulnerable del departamento de Cundinamarca”.